Application of Defense Science in Dealing with Ecological Damage in Indonesia - Firdaus, Mochammad Ferdion; Sudarya, Agus; Deksino, George Royke (International Journal of Global Community, 2023)
Based on the various indices, Indonesia’s ecological status is in a low - medium environmental condition and has sufficient potential for ecological damage. However, the way governments have dealt with ecological damage so far has been very limited, fragmented, and overlapping. On the other hand, various government policies so far have not adequately incorporated the defense and security paradigm. This research has novelty because research related to the application of defense science in responding to ecological damage has never been done in Indonesia. This research is supposed to reveal the inhibiting and supporting factors of defense strategy so that ecological damage as a non-military threat can be countered so that the security of the nation and the integrity of the state can be defended. This research is a qualitative study that attempts to build meaning about a phenomenon based on the views of the interviewees. The data collection methods used are interviews and document studies. The results of the analysis of several ecological indices from 2018 to 2020 showed that there has been a decline in the quality of ecosystems in several regions. This condition in the long term can threaten the existence of humans and other living organisms. This very high risk must be faced by creatures that live outside conservation areas, of which there are only about 30% in Indonesia. Based on that point, it can be said that Indonesia is encountering potential Ecological Damage which is also a defense threat. The threat of Ecological Damage will affect national defense if the Government does not take the proper actions. Therefore, the intervention needed at the present is not enough with only an environmental science or sustainable development approach. Defense Science must be applied to contribute to solving this problem because it can increase national readiness that can encourage awareness of all sectors. The realization of the application of defense science in overcoming ecological damage is through central government defense management which includes planning, institutionalization, direction, coordination, and supervision between relevant ministries